Yield Performance of Fine Aromatic Rice in Response to Variety and Level of Nitrogen - Chowdhury, SA; Paul, SK; Sarkar, MAR (Journal of Environmental Science and Natural Resources, 2016)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during June to December 2014 with a view to finding out the effect of variety and level of nitrogen on the yield performance of fine aromatic rice. The experiment consisted of three varieties viz. Kalizira, Binadhan-13 and BRRI dhan34, and six levels of nitrogen viz. 0, 30, 60, 90 kg N ha-1, USG 1.8 g 4 hills-1 (55 kg N ha-1) and USG 2.7 g 4 hills-1 (80 kg N ha-1). The experiment was laid out in a randomized complete block design with three replications. Variety, level of nitrogen and their interaction significantly influenced the yield of aromatic rice. The highest grain yield (3.33 t ha-1) was obtained from Binadhan-13 followed by BRRI dhan34 (3.16 t ha-1) and the lowest grain yield was found in Kalizira (2.11 t ha-1). In case of N, the tallest plant (140.3 cm), highest number of effective tillers hill-1 (11.40), grains panicle-1 (152.8), and grain yield (3.32 t ha-1) were obtained when fertilized with USG 1.8 g 4 hills-1 and the lowest values were found in 0 kg N ha-1. Therefore, Binadhan-13 fertilized with USG 1.8 g 4 hills-1 (55 kg N ha-1) appeared as the promising practice for appreciable grain yield. J. Environ. Sci. & Natural Resources, 9(1): 41-45 2016